Seismic behaviour of tunnels with different soil types and depths - Ku Sulaiman, Ku Safirah (2010)
Effect of seismic wave towards the tunnel as underground structure could cause unforeseeable damages during earthquake event. The waves that transmitted through the soil medium would affect the behaviour of the tunnel depending on the soil properties. The scope of this study will focus on tunnel structures in Malaysia; namely the SMART Tunnel and RAPID Tunnel. The objective of this study is to investigate the performance of the said tunnels under seismic load with different soil layer types and depths. These tunnels were modelled using finite element method (FEM) under dynamic analysis approach. Time history analyses were performed with several peak ground acceleration values, ranging from 0.05g, 0.10g, 0.15g, 0.19g and 0.25g. From this study, it was revealed that different soil properties surrounding the tunnel would affect the seismic behaviour of underground tunnel significantly. Nevertheless, both tunnels are capable to resist the earthquake loading compared with the design capacity of the tunnels.